Utilizing Performance Measurement in Physical Testing for Volleyball Using an Application - Qodri, Edwin; Hartati, Hartati; Aryanti, Silvi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research, titled "Utilization of Physical Test Measurements in Volleyball Using an Application for Students at Palembang 13 Public Junior High School," aims to establish normative categories for assessing physical test results in volleyball through the application. The critical components of physical fitness in volleyball, including endurance, speed, strength, and explosive power, are the focal points of this quantitative study employing a descriptive research design. The study involved 30 participants from the volleyball extracurricular program at Palembang 13 Public Junior High School, comprising 16 male and 14 female students. Various test instruments were employed for data collection, such as the bleep test for endurance, the 30-meter run for speed, 1-minute push-ups for arm strength, sit-up test for abdominal muscle strength, and vertical jump test for muscle explosive power. The research took place at Palembang 13 Public Junior High School, with collaboration from a member of the Teachers' Forum for Physical Education, Sports, and Health Education City of Palembang. Results indicated that the average physical condition of volleyball extracurricular students at Palembang 13 Public Junior High School falls into the very good category (18.6%), good category (3.8%), fair category (21%), less than average category (28.8%), and very less than average category (26.4%). In conclusion, the overall physical condition of these students is assessed as poor, with a percentage of 28.8%. The intention of this research is to serve as a basis for evaluation and raise awareness among students, encouraging them to continually enhance and maintain their physical fitness for optimal performance.